Editorial - Sarapura Sarapura, Mercedes Milagro (2023)
A point has been reached on the path of the accelerated journey of human development with the use of new communication technologies, from which one can contemplate, not without fascination and intrigue, the beginning of said development, its transit and the stage where you are currently; panoramicperspective that in itself raises numerous questions.